A Comparative Metabolomic Analysis Reveals Difference Manufacture Suitability in “Yinghong 9” and “Huangyu” Teas (Camellia sinensis) - Mei, Xin; Lin, Chuyuan; Wan, Shihua; Chen, Baoyi; Wu, Hualing; Zhang, Lingyun (Frontiers in Plant Science, 2021)
‘Yinghong 9’ is a widely cultivated large-leaf variety in South China, and the black tea made from it has high aroma and strong sweet flavor. ‘Huangyuis’ a light-sensitive tea variety with yellow leaf. It was cultured from bud mutation of ‘Yinghong 9’, and has a very low level of chlorophyll during growing stage. Because chlorophyll is involved in carbon fixation and assimilation, the changes of photosynthesis might potentially affect the accumulation of flavor metabolites as well as the quality of ‘Huangyu’ tea. Although ‘Huangyu’ has golden yellow color and high amino acid content, the mechanism underlying the formation of leaf color and drinking value remains unclear. In order to reveal the differences of key metabolites in fresh and fermented leaves between ‘Yinghong 9’ and ‘Huangyu’, widely targeted metabolomics and GC-MS analysis were used. The results showed that tea polyphenols, total chlorophyll a and carotenoids were more abundant in ‘Yinghong 9’. Targeted metabolomics analysis indicated that kaempferol-3-glycosides were more abundant in ‘Yinghong 9’, while ‘Huangyu’ had higher ratio of kaempferol-3-glucoside to kaempferol-3-galactoside. Compared with ‘Yinghong 9’ fresh leaves, the contents of zeaxanthin, lutein palmitate, capsanthin, lutein dioleate and β-citraurin were significantly higher in ‘Huangyu'. The contents of α-farnesene, β-cyclocitral and nerolidol and trans-geranylacetone, which were from carotenoid degradation and involved in flowery-fruity-like flavour in ‘Huangyu’ fermented leaves, were higher than those of ‘Yinghong 9’. Our results indicated that ‘Huangyu’ was suitable for manufacturing non-fermented tea because of its yellow leaf and flowery-fruity-like compounds from carotenoid degradation.